CANCELLED ELECTIVE GENERAL SURGICAL OPERATIONS IN AYUB TEACHING HOSPITAL - Zafar, Arshad; Mufti, Tariq Saeed; Griffin, Samson; Ahmed, Sajjad; Ansari, Johar Ali (Journal of Ayub Medical College Abbottabad, 2007)
Background: Cancellation of operations in hospitals is a significant problem with far reaching consequences. This study was planned to evaluate reasons for cancellation of elective surgical operation on the day of surgery in Ayub Teaching Hospital, Abbottabad. Methods: From July 2006 to June 2007 the medical records of all the patients who had their operations cancelled on the day of surgery in all the three General Surgical units of Ayub Teaching Hospital, Abbottabad were audited prospectively. The number of operation cancelled and reasons for cancellations were documented. Results: 3756 patients were scheduled for surgery during the study period. 2820(75%) patients were operated upon. 936 (25%) operations were cancelled out of which 338(36%) were cancelled due to shortage of time, 296(31.6%) were cancelled due to medical reasons, 152(16.2%) were cancelled due to shortage of beds while 55(5.8%) were cancelled due to shortage of anaesthetists. Three operation lists were lost completely. The Anaesthetist cancelled 43%, Surgeon 39% while 18% of operations were cancelled due organizational reasons. Conclusion: Cancellation of patients on operation lists occupy a substantial population (25%) of cases. Majority of cancellation were due to reasons other than patients medical conditions. Better management could have avoided most of these cancellations. Keywords: Surgical Operations.